2021
DOI: 10.1080/20477724.2021.1890887
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 randomized study on chloroquine, hydroxychloroquine or ivermectin in hospitalized patients with severe manifestations of SARS-CoV-2 infection

Abstract: Objective : Given the urgent need for strategies to minimize the damage caused by this pandemic, this study performed a randomized, double-blind phase 2 study to assess the safety of the effectiveness of chloroquine (CQ), hydroxychloroquine (HCQ) or ivermectin in severe forms of COVID-19, in addition to identifying predictors of mortality in this group of patients. Methods : Phase 2, double-blind, randomized study to assess the safety and efficacy of enteral CQ, HCQ or iverme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 39 publications
4
49
0
1
Order By: Relevance
“…However, other risk factors like the patient's age, serum ALT, creatinine, ferritin, and CRP being significantly related to all‐cause mortality may be attributable to the small dose of ivermectin. Accessible pharmacokinetic evidence from clinically significant and excessive dosage trials indicates that the concentration of ivermectin needed to suppress SARS‐CoV‐2 in humans with known dosing regimens is unlikely to be reached in serum and tissue 20–30 . Pott‐Junior et al 24 as well as Babalola et al 25 supported our results that higher doses of ivermectin may have a greater antiviral effect, but also showed that supra‐lethal toxic doses are unnecessary to inhibit viral replication.…”
Section: Discussionsupporting
confidence: 84%
“…However, other risk factors like the patient's age, serum ALT, creatinine, ferritin, and CRP being significantly related to all‐cause mortality may be attributable to the small dose of ivermectin. Accessible pharmacokinetic evidence from clinically significant and excessive dosage trials indicates that the concentration of ivermectin needed to suppress SARS‐CoV‐2 in humans with known dosing regimens is unlikely to be reached in serum and tissue 20–30 . Pott‐Junior et al 24 as well as Babalola et al 25 supported our results that higher doses of ivermectin may have a greater antiviral effect, but also showed that supra‐lethal toxic doses are unnecessary to inhibit viral replication.…”
Section: Discussionsupporting
confidence: 84%
“…There were 9 RCTs comprising of 1788 patients included in this systematic review and meta-analysis [ Fig. 1 ] [ [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] ]. Baseline characteristics of the included studies can be seen in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The underlying mechanism for this observation is unclear and requires further investigation. However, this observation might be due to 100% severe COVID-19 in two studies which enroll high percentage of hypertension (Galan et al [ 24 ] and NCT04646109 [ 26 ]), also these studies did not clearly report the presence of coronary artery disease or heart failure, which are important complications of hypertension. Thus, the finding might also be a coincidence or an indicator of other end organ complications.…”
Section: Discussionmentioning
confidence: 99%
“…The situation is aggravated by President Jair Messias Bolsonaro's solid support base, which endorses the use of these drugs. After all, the phosphoethanolamine episode in 2016 was a preview of the chloroquine-hydroxychloroquine-ivermectin hype of 2020, which have no proven efficacy in the treatment of COVID-19 and have several adverse effects [83][84][85][86][87][88][89]. However, the backlash was not so high back then as it was in 2020, and the phosphoethanolamine case did not draw the attention of the Brazilian population, in general.…”
Section: The Brazilian President: a Positive Case For Covid-19mentioning
confidence: 99%